COMPARISON OF GEOSTATISTICAL METHODS FOR MODELING INFILTRATION TYPE URANIUM DEPOSITS - Aizhulov, D.Ye.; Tungatarova, M.S. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
Filtration process occurring during the formation of infiltration type deposits largely affects the geometry and content of uranium deposits, which creates a challenge when conventional methods of geostatistics are applied for geomodelling purposes. Verification of these methods is practically impossible since true picture of the deposit is never known. In this work authors use a synthetic model generated through reactive transport simulation accounting for specific characteristics inherent in deposits, which formed via infiltration process. Two conventional methods were tested: inverse distance weighting method and the method of kriging. Comparison shows, that in terms of resource estimation and if intrinsic parameters of the method are chosen correctly, inverse distance method can provide a higher accuracy as compared to kriging with various number of exploratory wells used.